Estudo das estruturas de discordâncias cristalinas em arseneto de gálio - Alexandre Jose Medeiros do Nascimento (2009)
We employ ab initio calculations to investigate 90º partial dislocations ingallium arsenide. In a binary semiconductor like GaAs, two types of dislocations are present. In the a(ß) dislocation, there are two lines of arsenic (gallium) atoms on each side, bordering the geometric center of the dislocation core. For both the a ß and dislocations, we consider the energetics and electronic states of the quasi-fvefold (QF), the single- period (SP), and the double-period (DP) models that have been considered in the literature for 90.partials in semiconductors. In our calculations, we obtain the reconstruction energy, from the unreconstructed QF to the reconstructed SP, and the energy diference between the SP and DP cores, individually for each one of the a and ß dislocations. Given the presence of like-atom As-As (Ga-Ga) bonds along the core in the 90. a(ß)dislocation, in the QF, SP, and DP geometries,these are expected to be metallic, since As-As (Ga-Ga) bonds act as half-acceptors (half-donors) in GaAs. In view of that, we also considerantisite-doped models, in which one in every four As (Ga) atoms along the core of the a(ß)dislocation is replaced by a Ga (As) atom, in order to restore bond-stoichiometry in the core, in attempt to obtain semiconducting cores. The energetics of these bond-stoichiometric cores is compared with that of the QF, SP, and DP models.